(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Universal Design or ‘Accessibility for All’ is the design of a product or creation that meets the requirement and reaches the goals for people, which including disabled-bodies as well as the abled-bodies. Ergonomics is defined as a design to reduce human error, increase efficiency and improve safety and provides comfort in between people and the product. Universal design means segregation of special, separate designs with the normal design said that the majority of users can use them without feeling out of place. It is identified that some of the special groups all different kinds of designs would often make people feel different from others, the removal of which is essential in case of Universal Design. The major focus of this research is on the indoor spaces in providing measurement of operations and comfort in an indoor area such as the idea of research with respect to the ergonomics of Universal design which take into account within a qualitative research method of case study evaluation.